2022
DOI: 10.3390/v14050900
|View full text |Cite
|
Sign up to set email alerts
|

Early Treatment Consideration in Patients with Hepatitis B ‘e’ Antigen-Positive Chronic Infection: Is It Time for a Paradigm Shift?

Abstract: Chronic hepatitis B (CHB) is associated with significant morbidity and mortality, due to the adverse sequelae of cirrhosis and hepatocellular carcinoma (HCC). To date, antiviral therapy has been reserved for patients with ostensibly active liver disease, fibrosis or cirrhosis, and/or increased risk of HCC. Historically, patients with hepatitis B ‘e’ antigen (HBeAg)-positive chronic infection, were not offered antiviral therapy. Nevertheless, there has been compelling evidence emerging in recent years, demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…It appears that in CHB mothers with multiple pregnancies, a one‐off measurement of HBV DNA at the index pregnancy (first antenatal visit) may be sufficient in healthcare settings with limited resources, where repeat HBV DNA measurements at subsequent pregnancies would be unnecessary as HBV DNA levels rarely cross category from low to high viremia. On the other hand, as the current HBV treatment paradigm shifts towards an earlier treatment approach, 28 NUCs are likely to be continued beyond the suggested post‐partum period of prophylaxis, especially if future pregnancies are planned.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that in CHB mothers with multiple pregnancies, a one‐off measurement of HBV DNA at the index pregnancy (first antenatal visit) may be sufficient in healthcare settings with limited resources, where repeat HBV DNA measurements at subsequent pregnancies would be unnecessary as HBV DNA levels rarely cross category from low to high viremia. On the other hand, as the current HBV treatment paradigm shifts towards an earlier treatment approach, 28 NUCs are likely to be continued beyond the suggested post‐partum period of prophylaxis, especially if future pregnancies are planned.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HBeAg plays a key role in the host-virus interplay, particularly at the stage of viral antigen presentation and recognition by CD4 + T cells ( 33 ). During the process of clinical treatment, HBeAg clearance or HBeAg seroconversion can reflect viral control by the host, which is usually considered as one of the evidence of successful antiviral response ( 34 ) and/or reduced virus replication ( 34 ) and is believed to mark the end of immune-mediated liver damage ( 35 , 36 ). Interestingly, patients who were HBeAg positive had significantly higher IFIT3 mRNA levels than did HBeAg-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations for antiviral treatment of women before, during and after one or more pregnancies need to be informed by wider programmatic decisions about HBV treatment in all adults, with consideration of the potential individual- and population-level benefits of lowering the DNA threshold that determines eligibility. [71] , [72] , [73] In addition to reducing the risk of long-term liver disease in the individual, future strategies that endorse ongoing maternal antiviral therapy would also reduce MTCT risk for subsequent pregnancies, tackle the risk of horizontal transmission events within households, and abrogate the risk of severe liver flares associated with NA cessation. The optimal strategy will require pre-treatment HBV DNA quantitation, and the infrastructure to provide ongoing clinical monitoring and access to treatment for the mother; achieving this in practice is currently challenging in many settings but must be scaled up.…”
Section: Maternal Interventions: Challenges and Data Gapsmentioning
confidence: 99%
“…The cost of generic TDF (frequently <50 USD/per year in many countries) or, in the future generic TAF, should not be a barrier to treatment. [71] , [72] , [73] …”
Section: Maternal Interventions: Challenges and Data Gapsmentioning
confidence: 99%